P‐Coumaric acid, a dietary polyphenol ameliorates inflammation and curtails cartilage and bone erosion in the rheumatoid arthritis rat model. (25th July 2017) - Neog, Manoj Kumar; Joshua Pragasam, Samuel; Krishnan, Moorthy; Rasool, Mahaboobkhan
Abstract: This study was designed to explore the underlying mechanism of p ‐coumaric acid (CA), a dietary polyphenol in adjuvant‐induced arthritis (AIA) rat model with reference to synovitis and osteoclastogenesis. Celecoxib (COX‐2 selective inhibitor) (5 mg/kg b.wt) was used as a reference drug. CA remarkably suppressed the paw edema, body weight loss and inflammatory cytokine and chemokine levels (TNF‐α, IL‐1β, IL‐6, and MCP‐1) in serum and ankle joint of arthritic rats. Consistently, CA reduced the expression of osteoclastogenic factors (RANKL and TRAP), pro‐inflammatory cytokines (TNF‐α, IL‐1β, IL‐6, and IL‐17), and inflammatory enzymes (iNOS and COX‐2) in arthritic rats. However, OPG expression was found elevated. Besides, the abundance of transcription factors (NF‐κB‐p65, and p‐NF‐κB‐p65, NFATc‐1, and c‐Fos) and MAP kinases (JNK, p‐JNK, and ERK1/2) expression was alleviated in CA administered arthritic rats. In addition, CA truncated osteoclastogenesis by regulating the RANKL/OPG imbalance in arthritic rats and suppressing the RANKL‐induced NFATc‐1 and c‐Fos expression in vitro . Radiological (CT and DEXA scan) and histological assessments authenticated that CA inhibited TRAP, bone destruction and cartilage degradation in association with enhanced bone mineral density. Taken together, our findings suggest that CA demonstrated promising anti‐arthritic effect and could prove useful as an alternative drug in RA therapeutics. © 2017 BioFactors, 43(5):698–717, 2017